Psychic treatment and somatic treatment in children and adults - Del Volgo, Marie-José; Machado, Inesita (Clinical Styles. The Journal on the vicissitudes of childhood, 2004)
As a physiologist medical doctor, with functions in the hospitalar department of a laboratory of respiration functional research, I reserve some words, an instant of saying to all the patients who take a stock and have an evaluation of their respiratory function. It was in this scene that I found the patients involved in this research. All the four patients are affected by real somatic, clinically confirmed diseases. Treat the disease by medicine and treat the patient by psychoanalysis; it is the way in which the psychoanalytic treatment can continue to be practiced in a more and more techno-scientific and dehumanizing medicine.